Success in The Treatment of The Skeletal Cl III Cases (I) - Ayşegül Köklü; Zahir Altuğ; Neslihan Çağa; Meral Işık (Galenos Yayinevi, 1988)
There are several views about the beginning and the planning of the treatment and its prognosis in the skeletal Cl III cases. As shown in the cases, successful results can be obtained with the chin-cup therapy in the early period.